The Investigative Approach to Talking about Inclusion in Mathematics Teacher Education - Barros, Denner Dias [UNESP] (Open Book Publishers, 2022)
Looking at the range of diversity in the classroom is a necessary task for the teacher who seeks to teach from an inclusive perspective. More and more educational legislation has been authorised so that all students can have access to quality education. The use of landscapes of investigation in mathematics teacher education could become a practice that helps prospective teachers to reflect on future practices by taking into consideration the diversity of school contexts. In this chapter, reflections are made on the practices of two research projects, one for a doctorate and another for a Master’s degree. Working with investigative projects allowed prospective teachers to think about practices that take into account the particularities of this diversity. Furthermore, the dialogic perspective is highlighted as being essential in this process, as well as the ideas and visions of the prospective teachers invited to participate in their own professional education. It is hoped that this chapter can inspire prospective teachers to develop critical activities that allow for the participation of all students.